Sequence and structure alignment of paramyxovirus hemagglutinin-neuraminidase with influenza virus neuraminidase. - Colman, P M (1993)
A model is proposed for the three-dimensional structure of the paramyxovirus hemagglutinin-neuraminidase (HN) protein. The model is broadly similar to the structure of the influenza virus neuraminidase and is based on the identification of invariant amino acids among HN sequences which have counterparts in the enzyme-active center of influenza virus neuraminidase. The influenza virus enzyme-active site is constructed from strain-invariant functional and framework residues, but in this model of HN, it is primarily the functional residues, i.e., those that make direct contact with the substrate sialic acid, which have identical counterparts in neuraminidase. The framework residues of the active site are different in HN and in neuraminidase and appear to be less strictly conserved within HN sequences than within neuraminidase sequences.